CD95 and TNFα-induced apoptosis in liver metastases of colorectal carcinoma - Kasper, Hans-Udo; Konze, Elisabeth; Kern, Michael A.; Stippel, Dirk Ludger (In vivo, 2010)
Therapeutic options in patients with metastatic colorectal cancer are still limited. As apoptosis contributes to the overall sensitivity to radiotherapy or chemotherapy, a better understanding of the apoptotic process in metastatic tumour tissues is necessary.